The association of fasting plasma sulfur-containing compounds with BMI, serum lipids and apolipoproteins. - Elshorbagy, A; Valdivia-Garcia, M; Graham, I; Palma Reis, R; Sales Luis, A; Smith, A; Refsum, H (2012)
BACKGROUND AND AIM: Sulfur amino acids are recognized as potent modulators of lipid metabolism. Plasma total cysteine (tCys) is associated with fat mass, obesity and serum LDL-cholesterol and apolipoprotein (Apo)-B in large population studies. It is not known how fasting plasma concentrations of cysteine precursors and products relate to these associations in humans, given that sulfur-containing compounds (SCC) influence rodent weight gain and serum lipids. METHODS AND RESULTS: We investigated the cross-sectional associations of fasting plasma SCC (methionine, total homocysteine, cystathionine, tCys, taurine and total glutathione) with BMI and fasting serum lipids and apolipoproteins in 854 men and women with and without cardiovascular disease (CVD). In multiple linear regression analysis adjusted for age, gender, CVD and other SCC, neither methionine, taurine, nor total glutathione was associated with BMI. Plasma taurine was, however, inversely related to HDL-cholesterol (partial r = -0.12, p = 0.004) and its associated apoA1 (partial r = -0.18, p < 0.001). Plasma cystathionine correlated positively with triglycerides and BMI, while tCys positively correlated with total cholesterol, LDL-cholesterol (partial r = 0.20, p < 0.001) and its associated apoB. The associations of SCC with serum lipids were independent of BMI. tCys was also independently associated with BMI (partial r = 0.20, p < 0.001) after adjustment for other SCC, glucose, lipids and apolipoproteins. CONCLUSIONS: Fasting tCys is associated with BMI independently of metabolically related SCC. Elevation of plasma SCC is generally associated with an unfavorable lipid profile. The negative relations of plasma taurine with HDL-C and apoA1 deserve further investigation.